An Explanation of the Nature of civilization Based on Islamic Philosophy and Mysticism - Mohammad Hadi Homayoon; Ebrahim Khani (Religion & Communication, 2014)
Distinguishing civilization from other forms of human social entities on the basis of Islamic philosophy and mysticism is what is done in an expert manner in this article. It is concluded that civilization as a social unit is indeed, in the existential sense of the word, not arbitrary but an authentic one. This is because there exists an inseparable link between civilization's cultural background and its various social interactions in the sense that this latter signifies the emergence of the society's deep cultural possibilities, which dismisses any notion of arbitrariness as compared to other forms of human entities. To prove this, we have first offered an argument to explain the existential necessity of a particular kind of society, using Mulla Sadra's principle of subject-object identity and existential universal. Furthermore, to complete the argumentation by resolving a surrounding doubt, we have explained the status of social arbitrariness with a mystical and new basis in which human nature is used in an Islamic mystical manner. In the end, based on the explanation given about the nature of civilization, we have offered an ontological argument to prove the ultimate supremacy of the Islamic civilization centered upon velayat.